Mechanical characterisation of adhesive bonds in MEMS inertial sensors - Kendall, Peter (2018)
Micro-Electro-Mechanical Systems (MEMS) inertial sensors are used to measure acceleration and rate of angular rotation based on the deformation of a small sensitive structure, and are widely used from low-cost commercial to high-performance space and defence applications. Packaging processes can induce thermo-mechanical stresses and curvature within the MEMS die, leading to stressing and deformation of the sensitive MEMS element, which change over time and temperature. These effects cause performance changes over time and temperature, including zero-g offsets and bias and scale factor changes in MEMS accelerometers and quadrature bias changes in MEMS gyroscopes. The die bond, a small adhesive bond attaching the die to the package, can induce significant stresses and deformation in the die that have potential to cause these effects. This thesis focuses on the die curvature induced by the die bonding process, the mechanical properties of bonds, and investigates the changes in properties over temperature and time. The effects of bond design parameters are investigated to evaluate the performance of 4-dot and 9-dot bond shapes to reduce stress and reduce changes in curvature and mechanical properties over temperature and time. The behaviour of these bond shapes and the traditional square full coverage bond with thickness reductions is also investigated. Methods to characterise the mechanical properties of bonds are developed based on vibration testing of plain bonded dies, in bounce and shear directions, and using a single degree of freedom Kelvin-Voigt model with hysteretic damping. These methods are used to characterise different bond designs over the typical operating temperature range of a MEMS inertial sensor, in terms of apparent modulus and loss factor, as well as over time caused by thermal cycling and high temperature storage. White light interferometry is used to assess the die deformation induced by bonding and changes over time. The influence of imperfection effects on the dynamic response of the die is investigated, including coupling between translational and rotational coordinates and the resulting errors induced in the characterised properties. Finite Element models are developed to investigate the bond design parameters and their effect on bond induced curvature and translational die mode frequencies, along with their change over temperature. The results indicate the bond design parameters that are expected to reduce die curvature and property changes over temperature, as well as beneficial bond material properties. It was found that a bond material with a reduced thermal expansion coefficient provided the most significant reduction in die curvature from varying the bond material properties, and greatly reduced the percentage change in bond properties over temperature. It is thought that minimisation of performance effects would be achieved through matching of the bond and adherends thermal expansion rates. The 9-Dot bond was observed to induce the lowest die curvature of the bond shapes investigated and it was indicated that further discretisation would lead to further improvements. To reduce the temperature dependency of the bond properties, the bond should be designed such that it does not experience significant slenderness stiffening effects. To achieve the small thicknesses used in MEMS devices a very low shape factor is required, this can be achieved through a high perimeter to cross-sectional area ratio of the bond shape. Improvements and future works are proposed to allow full assessment of bond design effects experimentally and using finite element modelling. It is recommended for future investigations into die bond designs, to use larger-scale bonded samples, but maintaining slenderness ratios, to reduce the effects of imperfections and noise observed in the experiments, through reduced coupling and increased vibration response and die curvature.